The Dynamics of Multi-Stakeholder Collaboration: Challenges in Integrating the Pentahelix Model in Bojonegoro Geopark - Fitri Yuliana; Septi Wulandari; Rupiarsieh (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the form of multi-stakeholder collaboration in the management of the Bojonegoro Geopark using the Pentahelix approach. This study employed a qualitative method with data collected through interviews, observations, and documentation, while informants were selected purposively to represent the government, academia, business actors, community groups, and media. The findings indicate that although the five helixes are involved, their roles have not yet been integrated into a systematic collaborative framework. The government contributes through infrastructure provision and regulatory support but lacks a coordinating institution dedicated to geopark management. Academics provide research input, yet it has not formed a comprehensive basis for geosite interpretation. Business actors grow predominantly in recreational destinations, while community groups play essential operational roles but with uneven capacities. The media participates in promoting activities, although it has not succeeded in building a consistent geopark identity. Overall, this study concludes that weak inter-helix integration remains the primary challenge in developing the Bojonegoro Geopark. Therefore, strengthening institutional coordination, improving community capacity, and establishing an integrated communication strategy are essential for achieving sustainable geopark governance.